The Treatment Effects Of Open-Bıte Cases Wıth Combınatıon Of Actıvator, Occıpıtal Headgear, And Vertıcal Chın-Cap On Soft Tıssue Profıle - Zahir Altuğ; Meliha Rübendüz (Galenos Yayinevi, 1997)
This study was held on totally 68 lateral cephalograins and hand-wrist radiograms of 34 individuals. The materials of this study were obtained from the individuals at the beginning and at the end of treatment and controls. Nineteen of individuals were treatment group with skeletal and dental open-bite characteristics (13 girls, 6 boys). Fifteen of 34 individuals were nontreatment control group with skeletal and dental open-bite characteristics (7 girls, 8 boys). The nasolabial angle that is one of the most significant parameters of this investigation has been decreased due to the treatment efficiency, where it increases by devolopment. In addition to these changes, interlabial mucous length, lower lip mucous length and the distance between the lower lip and Steiner Soft Tissue Line has been decreased, also.